Pemanfaat Tepung Talas dan Tepung Kedelai sebagai Bahan Baku Pembuatan Pasta Fettucini - Khoiril Danastio Wijayanto; Alip Suroto; Ida Ayu Kade (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
The culinary industry is growing rapidly with the trend of product innovation, including the use of food waste. This study processed non-gluten taro flour as a healthier homemade pasta ingredient than instant pasta. The challenge of using taro flour is low binding, so it is necessary to modify or mix high gluten flour to improve the quality and ease of processing. This research focuses on the use of taro flour and soybean flour as ingredients for making pasta. Through sensory evaluation, the characteristics of taste, color, aroma, and texture were studied. The goal is to collect relevant and reliable data to determine the effect of adding taro flour on the quality of paste, so as to provide answers and solutions to research problems. The results showed that sample C scored the lowest on all indicators, while the highest scores varied: color, aroma, texture in sample A taste and overall in sample B. Experimental constraints included manual pasta cutting that was not neat and the dough was difficult to mix, taking a long time to achieve the texture of the khalis. Fettucini paste from taro flour and soybean flour is made through weighing, mixing with eggs, water, salt, kneading until smooth, grinding, cutting, and boiling. This product has a chewy texture, is pale yellowish, and is healthier because it is low in gluten. It tastes naturally savory with a typical soybean aroma, as well as a chewy texture but can be crumbly if the taro flour is excessive.